If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = (2x + -5)(x + 1)(x + -3) Reorder the terms: 0 = (-5 + 2x)(x + 1)(x + -3) Reorder the terms: 0 = (-5 + 2x)(1 + x)(x + -3) Reorder the terms: 0 = (-5 + 2x)(1 + x)(-3 + x) Multiply (-5 + 2x) * (1 + x) 0 = (-5(1 + x) + 2x * (1 + x))(-3 + x) 0 = ((1 * -5 + x * -5) + 2x * (1 + x))(-3 + x) 0 = ((-5 + -5x) + 2x * (1 + x))(-3 + x) 0 = (-5 + -5x + (1 * 2x + x * 2x))(-3 + x) 0 = (-5 + -5x + (2x + 2x2))(-3 + x) Combine like terms: -5x + 2x = -3x 0 = (-5 + -3x + 2x2)(-3 + x) Multiply (-5 + -3x + 2x2) * (-3 + x) 0 = (-5(-3 + x) + -3x * (-3 + x) + 2x2 * (-3 + x)) 0 = ((-3 * -5 + x * -5) + -3x * (-3 + x) + 2x2 * (-3 + x)) 0 = ((15 + -5x) + -3x * (-3 + x) + 2x2 * (-3 + x)) 0 = (15 + -5x + (-3 * -3x + x * -3x) + 2x2 * (-3 + x)) 0 = (15 + -5x + (9x + -3x2) + 2x2 * (-3 + x)) 0 = (15 + -5x + 9x + -3x2 + (-3 * 2x2 + x * 2x2)) 0 = (15 + -5x + 9x + -3x2 + (-6x2 + 2x3)) Combine like terms: -5x + 9x = 4x 0 = (15 + 4x + -3x2 + -6x2 + 2x3) Combine like terms: -3x2 + -6x2 = -9x2 0 = (15 + 4x + -9x2 + 2x3) Solving 0 = 15 + 4x + -9x2 + 2x3 Solving for variable 'x'. Combine like terms: 0 + -15 = -15 -15 + -4x + 9x2 + -2x3 = 15 + 4x + -9x2 + 2x3 + -15 + -4x + 9x2 + -2x3 Reorder the terms: -15 + -4x + 9x2 + -2x3 = 15 + -15 + 4x + -4x + -9x2 + 9x2 + 2x3 + -2x3 Combine like terms: 15 + -15 = 0 -15 + -4x + 9x2 + -2x3 = 0 + 4x + -4x + -9x2 + 9x2 + 2x3 + -2x3 -15 + -4x + 9x2 + -2x3 = 4x + -4x + -9x2 + 9x2 + 2x3 + -2x3 Combine like terms: 4x + -4x = 0 -15 + -4x + 9x2 + -2x3 = 0 + -9x2 + 9x2 + 2x3 + -2x3 -15 + -4x + 9x2 + -2x3 = -9x2 + 9x2 + 2x3 + -2x3 Combine like terms: -9x2 + 9x2 = 0 -15 + -4x + 9x2 + -2x3 = 0 + 2x3 + -2x3 -15 + -4x + 9x2 + -2x3 = 2x3 + -2x3 Combine like terms: 2x3 + -2x3 = 0 -15 + -4x + 9x2 + -2x3 = 0 The solution to this equation could not be determined.
| 12a^2-4a-40=0 | | 3x^6-7x^2+5=0 | | 3x+4x+1=2 | | 8x^3+6x^2-17x+6=0 | | 58=2x-10 | | 16r^2+2r-5=0 | | 0=14x^4-x^2+49 | | -7p-10=-8-7x-6 | | 3y-13=5 | | .75x+.67=.875 | | 3-3n=-12 | | (x^2)=-1 | | f(x)=2x^2-12x+16 | | 0=x^4-1 | | .05x+x=1837000 | | 4x+5y+6z+7w=-5 | | 10x-30=535 | | 49w^2+12=0 | | 3x-4(x-3)=3x-3(2-x) | | Z=5z+-16 | | -.5x=-4.3 | | -3+17=-2(7x) | | 2x+10=3x-24 | | 25y+3=5-y | | 40+2(x+3)=8+3(2x+5) | | Z+7=5z+(-9) | | -lgx=2 | | 4(x+1)-2(3x+4)=-2(x-2) | | 0=16t^2-1444 | | 129000=.86x | | 12*1.3= | | 3y-18x=6 |